2017
DOI: 10.1021/acsomega.7b01061
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Vanadium Oxide Nanofibers with Variable Crystallinity and V5+/V4+ Ratios

Abstract: Tailoring the morphological, chemical, and physical properties of vanadium oxides (VOx) is crucial to optimize their performance in current and future applications. The present contribution proposes a new route to obtain VOx nanofibers with different V 4+ /V 5+ ratios and crystallinity. The method involves the exclusive electrospinning of water-free NH 4 VO 3 -saturated solutions including a reductant. Subsequent air-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 50 publications
(108 reference statements)
3
30
0
Order By: Relevance
“…The lines at 425 and 494 cm −1 might also be associated with V 4 O 9 , whereas the remaining bands should correspond to the signal from V 3 O 7 . The spectra of our samples are remarkably similar to those reported earlier for V 7 O 16 (Figure d), V 6 O 13 (Figure e), and the product of degradation of some samples (Figures b and a) . Therefore, we believe that V 3 O 7 was produced in all the disputable cases.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The lines at 425 and 494 cm −1 might also be associated with V 4 O 9 , whereas the remaining bands should correspond to the signal from V 3 O 7 . The spectra of our samples are remarkably similar to those reported earlier for V 7 O 16 (Figure d), V 6 O 13 (Figure e), and the product of degradation of some samples (Figures b and a) . Therefore, we believe that V 3 O 7 was produced in all the disputable cases.…”
Section: Resultssupporting
confidence: 89%
“…Although V 3 O 7 occupies much of the phase diagram, there are few reports of its formation. Recently, it has been produced in a form of nanofibers and nanoflowers . Raman scattering for the samples has been reported (Figure a,b).…”
Section: Vanadium Oxide Polymorphs: Structures and Raman Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The porous property observed in these Fe/Cu/V nano-catalysts contributed to the improvement of benzene oxidation efficiency using H 2 O 2(aq) with additional H 2 O proportions in CH 3 CN (Ramu et al, 2017;Wanna et al, 2019b), which is consistent with the effect of water-assisted benzene oxidation catalyzed by the molecular iron complex encapsulated in the zeolite (Yamaguchi et al, 2015). In addition, the powder XRD and selected area (electron) diffraction SAD-TEM analysis for V nr catalyst indicated that the crystal grew longer to rod shape with preferential (220) orientation that can be crucial for the related additional activities (Berenguer et al, 2017). The crystalline feature of Fe and Cu catalysts also exhibited a distinctive crystal arrangement that directly corresponded to the nature of the parental metal-oxide materials.…”
Section: Characterizations and Common Features Of The Fe/cu/v Nano-casupporting
confidence: 76%
“…The V 2p XPS spectrum was characterized to understand the surface oxidation state of the V 2 O 5 films ( Figure 2 b) with the Al Kα X-ray. The strong peak at the binding energy of 517 eV, which was assigned to the V 5+ of V 2 O 5 , was observed in both the bare V 2 O 5 and the NP-V 2 O 5 prepared using 40 mM PEG [ 38 , 39 , 40 ]. No significant changes in the XRD and XPS spectra were observed between the bare V 2 O 5 and NP-V 2 O 5 layers.…”
Section: Resultsmentioning
confidence: 99%